Hiérarchisations linguistiques et émergence de fragilités psychosociales : un aperçu chez les jeunes en milieu franco-albertain - Bahi, Boniface; Mulatris, Paulin (Minorités linguistiques et société, 2018)
Cette contribution analyse les conditions sociolinguistiques structurantes de la fragilité psychosociale des jeunes Franco-Albertains. Trois contextes émergent : l’anglo-dominance, la relation ambivalente avec le Québec et la francophonie non traditionnelle issue des programmes d’immersion ou de l’immigration. L’analyse des données relatives à ces contextes, et en référence aux notions de hiérarchie linguistique et de fragilité psychosociale, révèle des sentiments ambigus de fragilité. Parallèlement à la fragilité, d’autres sentiments se manifestent chez les jeunes Franco-Albertains, telle la résistance qui apparaît comme leur compétence à surmonter l’adversité en s’inspirant de l’histoire de leur famille ou de leur groupe ethnique. Le recours à cette histoire révèle l’insuffisance des appuis psycho-sanitaires institutionnels. Ainsi, le théâtre des variations linguistiques, ou autrement dit, des niveaux de langage, entre jeunes en milieu franco-albertain illustre-il une problématique majeure, celle invitant à rechercher de nouveaux lieux socioculturels et sociolinguistiques de santé mentale. Mots-clés : hiérarchie linguistique, fragilité psychosociale, santé mentale, anglo-dominance, Franco-Albertains

Points saillants sur la santé mentale des jeunes franco-canadiens d’est en ouest du pays : le témoignage de nos assistantes de recherche - Benoit, Monique; Beaton, Ann. M. (Minorités linguistiques et société, 2018)

Accès aux services de santé et d’interprète accompagnateur : l’expérience des communautés minoritaires à faible densité de francophones au Canada. Rapport de recherche-Projet INTACC - de Moissac, Danielle (Société Santé en français, 2016)

Access to health and interpreter-companion services – the experience of sparsely populated Francophone minority communities in Canada - de Moissac, Danielle (Société Santé en français, 2016)

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Perceptions of healthy aging among Francophone older adults living in Edmonton, Alberta [master's thesis, University of Alberta] - Esso, Christelle. M.-C. (University of Alberta, 2013)

L’accès aux services de santé en français et leur utilisation en contexte francophone minoritaire. Rapport final - Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques et Société Santé en français, 2014)

Gaps in knowledge and practices of malaria prevention in Francophone African immigrants in Metropolitan Edmonton - Hanna, Taylor A.; Ahmed, Ali; Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Youssef; Petrick, Ryland; Vincent, Etienne; El Hafid, Mélanie; Hawkes, Michel T.; Ravi, Srilata; Gnidehou, Sedami (Malaria Journal, 2022)
Background Important knowledge gaps exist in the understanding of the management of the risks of imported malaria in Canada among Francophone immigrants from sub-Saharan Africa (FISSA). The aim of this cross-sectional study was to investigate the malaria related-knowledge, attitude and practices (KAP) of FISSA in Edmonton, where these immigrants are in an official minority language situation and the impact of language barriers on these factors. Methods A structured survey was used to examine the KAP of 382 FISSA in the Edmonton area from 2018 to 2019. Fisher’s Exact Test was applied to determine if there were associations between knowledge of malaria and different risk factors. Results Almost all FISSA (97%) had an accurate knowledge of fever as the key symptom of malaria. Interestingly, 60% of participants identified bed nets as a preventive method and only 19% of participants had accurate knowledge of malaria transmission. An accurate knowledge of symptoms was significantly associated with a high perceived risk of contracting malaria [odds ratio (OR) 4.33, 95% confidence interval (CI) 1.07–20.62]. Furthermore, even though 70% of FISSA had a high perceived risk of contracting malaria in endemic regions, only 52% of travellers had a pre-travel medical encounter. Importantly, language was not the predominant reason for not seeking pre-travel medical advice, although 84% of respondents chose French as their official language of preference when seeking medical advice. Having a French-speaking physician was correlated with satisfactory prevention knowledge (OR 1.96, 95% CI 1.16–3.35). With respect to health-seeking behaviour, 88% of respondents with a child < 5 years of age would seek medical care for fever in the child after travel to sub-Saharan Africa (SSA). Conclusion This study highlights that factors other than knowledge, risk assessment, and language might determine the lack of compliance with pre-travel medical encounters. It underscores the need for effective strategies to improve this adherence in minority settings.

Perception du contexte linguistique et culturel minoritaire sur le vécu de la grossesse - Lacaze-Masmonteil, Thierry; Leis, Anne; Lauriol, Emmanuelle; Normandeau, Joane; Moreau, Denise; Bouchard, Louise; Vaillancourt, Cathy (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif Dans une perspective de santé publique, le suivi de grossesse et la période périnatale exigent une communication de qualité et des services de santé qui tiennent compte du contexte dans lequel ces femmes évoluent. Or, des défis d’accès aux services de santé en français en situation minoritaire au Canada ont été documentés. Cette étude pilote a pour objectif de mieux cerner les perceptions et le vécu de femmes enceintes francophones vivant au Canada dans un contexte linguistique minoritaire Méthodes Étant donné la nature exploratoire du questionnement, une étude descriptive alliant des méthodes quantitative et qualitative a été mis en œuvre en Alberta et au Nouveau-Brunswick, dont les populations sont de 2 % et 33 % francophones, respectivement. Deux entrevues semi-structurées et une série de questionnaires ont été administrées auprès de 21 femmes enceintes au début du troisième trimestre de grossesse et à six semaines après la naissance. Une analyse descriptive des questionnaires a permis de dresser le profil et les caractéristiques des participantes, et les entrevues qualitatives, transcrites, codées et analysées de façon inductive par quatre lecteurs indépendants, ont fait ressortir plusieurs thèmes Clés en rapport avec leurs expériences. Résultats La plupart des participantes se sont dites bilingues et la langue ne semble pas avoir été un enjeu majeur dans l’évaluation des services de santé reçus sauf en situation de stress et lors de certaines périodes critiques de la grossesse et de l’accouchement. Par contre, près d’un tiers des participants se disent insatisfaites des services de santé reçus et l’insuffisance de suivi en français est mentionnée comme un des facteurs contribuant à cette insatisfaction. Conclusion Les services de santé sont préférés dans la langue maternelle des femmes mais reçus dans la langue de la majorité la plupart du temps. En situation de stress ou de complication de grossesse, les témoignages des participantes semblent indiquer que la communication en français est un facteur essentiel d’un suivi de grossesse de qualité. Une étude comparative permettrait de mieux distinguer l’impact spécifique de la langue dans l’expérience vécue des femmes enceintes.

Enjeux du vieillissement chez les Africains en milieu francophone minoritaire canadien - Mulatris, Paulin; Bahi, Boniface (Alterstice, 2014)
Les enjeux du vieillissement des populations francophones d’origine africaine subsaharienne sont très peu connus. Une analyse de données qualitatives portant sur le vécu socioculturel et les déterminants de la santé, obtenues au moyen d’entrevues semi-structurées auprès d’immigrants francophones africains subsahariens des régions urbaines d’Edmonton et Calgary, permet de constater que cette population cumule des défis culturels et économiques qui les poussent à développer un mode de vie inapproprié aux conditions d’un vieillissement en santé. La nécessité que ces Néo-Canadiens développent des habitudes de vie adaptées mène à une réflexion sur les conditions socioéconomiques auxquelles ils font face et sur l’adaptation culturelle des soins.

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

Étude de l’impact de déterminants psycho-socio-environnementaux sur la santé physique et mentale des femmes enceintes vivant dans un contexte linguistique et culturel minoritaire - Vaillancourt, Cathy; Lacaze-Masmonteil, Thierry (Francophonies d’Amérique, 2009)
La barrière linguistique réduirait le recours aux services préventifs, l’accès aux services basés sur la communication et augmenterait le recours aux services d’urgence. Les femmes sont particulièrement à risque à cause de leurs besoins accrus de services de santé et de soutien psychosociaux durant la grossesse, l’accouchement et la période du post-partum. Cette étude vise à recueillir de l’information sur les expériences de maternité des femmes francophones (Canadiennes et immigrantes) du Nouveau-Brunswick et de l’Alberta. Les résultats de cette étude seront utilisés pour améliorer les soins de santé et l’accès à l’information pour les femmes enceintes en situation linguistique et culturel minoritaire.

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Research Component. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon. Executive summary - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Volet Recherche. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Quand le terrain informe les interventions communautaires. - van Kemenade, Solange; Tremblay, Éléonore; Benhamadi, Bey; Moussard, Aline; Michel, Jean Nephetaly (Minorités linguistiques et société, 2024)
L’Abécédaire d’un cerveau en santé – Sensibilisation à la démence dans l’Ouest et le Nord est un projet chapeauté par RésoSanté Colombie-Britannique et mis en oeuvre en partenariat avec les réseaux de Santé en français de la Saskatchewan, de l’Alberta et du Yukon. Ses objectifs étaient : a) produire des connaissances pour mieux comprendre la problématique de la démence et son impact dans les communautés francophones dans les provinces et le territoire ciblés; b) prévenir la démence et réduire la stigmatisation des personnes atteintes de troubles neurodégénératifs. Cet article se concentre sur le volet recherche du projet qui a accompagné l’intervention communautaire. Des entrevues semi-structurées (N=29) et un sondage en ligne (N=282) auprès des communautés francophones, des personnes proches aidantes, des intervenantes et des intervenants ainsi que du personnel oeuvrant dans les organisations de la francophonie ont été réalisées. L’étude a contribué à documenter la nécessité de services de prévention, de diagnostic, de soutien et de soins en français en matière de troubles neurocognitifs, à repérer des populations plus vulnérables et à recenser des bonnes pratiques. La recherche sur le terrain a éclairé les responsables et les partenaires du projet dans le choix des interventions communautaires appropriées en matière de prévention et de sensibilisation dans un contexte linguistique minoritaire. Mots-clés : troubles cognitifs, démence, francophones en situation minoritaire, interventions communautaires, Canada

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.